THE REVIVAL OF TRADITIONAL TECHNIQUES AND METHODS IN THE CONTEMPORARY DESIGN OF JADE PRODUCTS IN CHINA - Тан, Чжунянь; Пашкевич, К. Л. (Art and Design, 2023)
The aim of the article is to analyse the revival of traditional techniques and methods in the contemporary design of jade products in China during the 20th and 21st centuries, to identify the factors contributing to this revival, the influence of cultural heritage on contemporary jade design, and the role of modern technologies in the preservation and development of traditional craftsmanship. Methodology is based on a comprehensive study of the topic and includes: methods of analysis, synthesis, induction, the method of structural and systematic analysis of sources, historical and comparative methods. Secondary data will be obtained from a review of relevant literature, historical documents, and analysis of jade artefacts from different periods. The key factors of the revival of traditional techniques and methods in modern jade design are identified, the trends of preservation and popularization of cultural heritage in the context of modern production are analyzed. The main techniques used by contemporary designers in the creation of jade products are identified. On the example of the works of Chinese masters, the heredity of the symbolism of ancient jade products and their reflection in the modern design of jade products in China are studied. The influence of the revival of traditional techniques and motifs of jade art on the preservation of cultural heritage, market trends and the reaction of modern Chinese society is traced. The scientific novelty of the study lies in the comprehensive study of the revival of traditional techniques and methods in modern jade design in the context of China in the 20th and 21st centuries, for the first time considering a set of historical and cultural factors and the impact of government policy and industry initiatives on the integration of traditional and modern design elements in jade products. The materials of the article can be used in the study of the topic in the training of specialists in design and decorative and applied arts and in writing scientific papers. In addition, the study will provide insight into the preservation and popularisation of cultural heritage in the context of modern production, which will make a valuable contribution to other industries seeking to balance the traditional approach and innovation.